Karakteristik dan Bentuk Kode Etik Dakwah - Bukhari, Bukhari (Universitas Islam Negeri Imam Bonjol Padang, 2013)
In dakwah activity, there needs rules that agreed upon and binding in order to avoid obstacles in dakwah and the things that are not desirable. The rules are a code of ethics as a guide proselytizing da’i in dakwah. Code is written guidelines containing ethical norms that serve as guidelines to think, behave and act. Ethics codes are actually for dakwah, so that dakwah activity can be done well and does not cause unrest and clashes between da’i and among the public. Ethics and codes of conduct in carrying out propaganda should be maintained and implemented by da’i in order to reach the goal of dakwah effectively and efficiently.